METRICS, PUBLIC INDICATORS AND DEATHS BY HOMICIDE: AN ANALYSIS OF POSSIBLE RELATIONS IN MUNICIPALITIES IN SOUTHERN MINAS GERAIS BETWEEN 2010 AND 2021 - Barbosa, André Silveira; Pessanha, Gabriel Rodrigo Gomes (Seven Editora, 2025)
The objective of this research is to analyze possible relationships between metrics or indicators related to social assistance, citizenship, education, infrastructure, GDP per capita, total population, health, and urbanization in municipalities in southern Minas Gerais and their homicide death rates between 2010 and 2021. To this end, a quantitative methodological approach was employed, initially through a bibliometric study of the literature on the subject and subsequently through descriptive statistical analysis and linear regression. One of the results of this study was that homicide death rates decrease when there is an increase in budgetary effort for activities focused on population health, based on the figures presented by the southern Minas Gerais cities selected in this study. DOI: https://doi.org/10.56238/sevened2025.029-078